Best Answer

A "solution" is a pair of numbers ... one for 'x' and one for 'y' ... that make the equation

a true statement when you put them in place of 'x' and 'y'.

There are an infinite number of them.

Q: How many solutions are in x 3y 2 2x 6y -3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

the simplest form of 5x + 3y +2x - 6y is 7x-3y

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

2x - 3y = 62x = 3y + 63y = 2x - 6y = (2x - 6)/3y = (2/3)x - 2

5x + 6y + 3y - 2x you have to add like terms. add the y terms and then the x terms 9y + 3x this is your answer

Let's see. 2X + 3Y = 12 3Y = - 2X + 12 Y = -2/3X + 4 ---------------- 6Y - 4X = 2 6Y = 4X + 2 Y = 2/3X + 1/3 --------------------- Nope. They can't be. Plot a few points and see.

Related questions

6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y

the simplest form of 5x + 3y +2x - 6y is 7x-3y

Collect like terms: 2x + 3y + 3y - 5 - 6 2x + 6y - 11

5x -6y=-30 5x-6y=30 (2x+3y) (2x-3y)=30 4x+6y=30 4x=30 x=30/4

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

2x - 3y = 62x = 3y + 63y = 2x - 6y = (2x - 6)/3y = (2/3)x - 2

The equations are identical in value, ie the second is merely twice the first...

5x + 6y + 3y - 2x you have to add like terms. add the y terms and then the x terms 9y + 3x this is your answer

It is: 2(x+3y) when factored

Let's see. 2X + 3Y = 12 3Y = - 2X + 12 Y = -2/3X + 4 ---------------- 6Y - 4X = 2 6Y = 4X + 2 Y = 2/3X + 1/3 --------------------- Nope. They can't be. Plot a few points and see.

20x2 + 22xy + 6y2 = 20x2 + 10xy + 12xy + 6y2 = 10x(2x + y) + 6y(2x + y) = (2x + y)(10x + 6y) = 2(2x + y)(5x + 3y)

It is 324xy3